Prothrombin Scranton: Substitution of an Amino Acid Residue Involved in the Binding of Na+ (LYS-556 to THR) Leads to Dysprothrombinemia - Sun, William Y.; Smirnow, David; Jenkins, Mallory L.; Degen, Sandra J. F. (Thrombosis and Haemostasis, 2001)
Several members of a family from Scranton, Pennsylvania were identified to have normal levels of prothrombin antigen while their prothrombin clotting activity was approximately 50% of normal. There has been no previous history of bleeding or other clinical manifestations in this family. The genomic DNA from the proband was amplified for all exons in the prothrombin gene and analyzed by single strand conformation polymorphism (SSCP)/heteroduplex analysis followed by DNA sequence analysis and restriction enzyme digestion. A mutation at nucleotide 20040 in exon 14 was identified and confirmed by restriction enzyme digestion. This mutation results in the substitution of Thr for Lys at amino acid 556. Amino acid 556 has been reported as one of the key residues for the binding of Na+ in the thrombin portion of the protein.
Keywords: Prothrombin; dysprothrombinemia; abnormal prothrombin; Na+ binding; SSCP/heteroduplex analysis